2012
DOI: 10.1155/2012/504952
|View full text |Cite
|
Sign up to set email alerts
|

NFκB and AP-1 Drive Human Myometrial IL8 Expression

Abstract: The uterine expression of the chemokine IL8 increases dramatically with the onset of labour both at term and preterm. The IL8 promoter contains binding sites for the transcription factors nuclear factor-kappa B (NFκB), activator protein-1 (AP-1), and CCAAT/enhancer-binding protein (CEBP). In this study we investigated the roles of these transcription factors in IL1B regulation of the IL8 gene in human myometrium. Using chromatin immune precipitation (ChIP) assay, we showed that each of NFκB, CEBP, and AP-1 bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 35 publications
4
44
0
Order By: Relevance
“…Another protein firmly involved in angiogenesis of neuroblastoma is vascular endothelial growth factor (VEGF) (5,6). As expected, one of the control levels is transcription-related to the interaction between IL-8 and VEGF promoters and different transcription factors, such as NF-κB, AP-1 and C-EBP/NF-IL-6 (7)(8)(9)(10)(11)(12). In addition, the expression of IL-8 and VEGF genes may be under the control of epigenetic mechanisms, such as those regulated by microRNAs in cancer, differentiation and inflammatory processes (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 89%
“…Another protein firmly involved in angiogenesis of neuroblastoma is vascular endothelial growth factor (VEGF) (5,6). As expected, one of the control levels is transcription-related to the interaction between IL-8 and VEGF promoters and different transcription factors, such as NF-κB, AP-1 and C-EBP/NF-IL-6 (7)(8)(9)(10)(11)(12). In addition, the expression of IL-8 and VEGF genes may be under the control of epigenetic mechanisms, such as those regulated by microRNAs in cancer, differentiation and inflammatory processes (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, the observed association between increased JNK signaling and EGR-1 protein in obese placenta may suggest that EGR-1 can mediate obesity-induced placental inflammation and warrants further investigation. DNA binding sites for NF-B, AP-1, and EGR-1 have been described in the promoters of a number of inflammatory cytokine genes including TNF␣ (73), IL-6 (13,26,35) and IL-8 (26,33), indicating direct regulation of cytokine expression by these transcription factors. Importantly, studies have shown that combinations of transcription factor binding are required for transactivation of proinflammatory cytokine expression in an inducer-specific manner (11,13,21,29,73,77).…”
Section: E9mentioning
confidence: 99%
“…The human IL-8 gene promoter contains a number of regulatory cis elements that are activated by the interaction with AP-1, CCAAT/enhancer-binding protein (C/EBP), and nuclear factor-B (NF-B) (15). The transcription start site of the IL-8 gene is located 101 bp upstream of the translation site.…”
Section: Effect Of Srsf3-tr On Arsenite-stimulated Il-8 Productionmentioning
confidence: 99%